ANALISIS FAKTOR-FAKTOR RENDAHNYA PARTISIPASI ANGGOTA DALAM ORGANISASI KARANG TARUNA TINGKAT KABUPATEN CIREBON - Diva Dwi Lestari; Ali Jufri; Sylvani (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to identify and analyze the factors causing low participation among members in the Karang Taruna organization in Cirebon Regency. Member participation in community-based organizations, particularly Karang Taruna, plays a crucial role in improving social welfare and empowering the youth. However, in recent years, there has been a significant decline in member participation in Karang Taruna Cirebon Regency. This study employs a qualitative approach with a case study method, involving in-depth interviews, observations, and document analysis. The research findings indicate that low participation is caused by several factors, including low motivation, ineffective internal communication, lack of communicative leadership, lack of recognition for members' contributions, limited facilities and funds, and activities that are not relevant to the needs of the youth. Based on these findings, the study recommends that Karang Taruna management improve internal communication, involve members in decision-making, provide recognition, and develop activities that are more relevant to the needs of young people.